Rapalogs downmodulate intrinsic immunity and promote cell entry of SARS-CoV-2 - Shi, Guoli; Chiramel, Abhilash I.; Li, Tiansheng; Lai, Kin Kui; Kenney, Adam D.; Zani, Ashley; Eddy, Adrian C.; Majdoul, Saliha; Zhang, Lizhi; Dempsey, Tirhas; Beare, Paul A.; Kar, Swagata; et al. (The Journal of clinical investigation, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in immunocompromised individuals is associated with prolonged virus shedding and evolution of viral variants. Rapamycin and its analogs (rapalogs, including everolimus, temsirolimus, and ridaforolimus) are FDA approved as mTOR inhibitors for the treatment of human diseases, including cancer and autoimmunity. Rapalog use is commonly associated with an increased susceptibility to infection, which has been traditionally explained by impaired adaptive immunity. Here, we show that exposure to rapalogs increased susceptibility to SARS-CoV-2 infection in tissue culture and in immunologically naive rodents by antagonizing the cell-intrinsic immune response. We identified 1 rapalog (ridaforolimus) that was less potent in this regard and demonstrated that rapalogs promote spike-mediated entry into cells, by triggering the degradation of the antiviral proteins IFITM2 and IFITM3 via an endolysosomal remodeling program called microautophagy. Rapalogs that increased virus entry inhibited mTOR-mediated phosphorylation of the transcription factor TFEB, which facilitated its nuclear translocation and triggered microautophagy. In rodent models of infection, injection of rapamycin prior to and after virus exposure resulted in elevated SARS-CoV-2 replication and exacerbated viral disease, while ridaforolimus had milder effects. Overall, our findings indicate that preexisting use of certain rapalogs may elevate host susceptibility to SARS-CoV-2 infection and disease by activating lysosome-mediated suppression of intrinsic immunity.